(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2023)
This text was born from the dialogues with my colleague Liliana Pérez Recio about the execution of the guided tour in the permanent exhibition at El Arca Theater-Museum of Puppets, whose museological script we created jointly. I wrote her a letter. This turned out to be a story that allows us to observe various problems related to the operation of the museum, its purposes and policies, its exhibition solutions and the way in which we are building a history of the puppet from our knowledge, but also from our shortcomings and sleeplessness. In this way, it is narrated how the practice has evolved the way of conducting the guided tour of the museum. The epistolary text led to addressing the interpretation of heritage as a function of the museum, for a better understanding of the process that we initiated empirically and intuitively, based on theatrical principles that are part of the intangible heritage of the founders of the collection in direct dialogue with the museum theme.